KONDISI KEJIWAAN TOKOH UTAMA “OTOKO” DALAM NOVEL UTSUKUSHISA TO KANASHIMITO KARYA KAWABATA YASUNARI ( Sebuah kajian psikoanalisis ) - Budi Mulyadi (Universitas Diponegoro, 2013)
ABSTRACT This research is entitled The condition spirit of Otoko as the main figure in novel Utsukushisa to Kanashimi to written by Kawabata Yasunari published in 1965. The purpose of this research is to analyze the condition spirit of Otoko as the main figure centered round on her spirit conflict, death instinct, and anxious The Approach used to resolve the problem is Sigmund Freud psychoanalysis. The research show Otoko as the main figure in this novel has many spirit conflict caused by several happening that she experienced since she was young until grown-up. Her spirit conflict caused by two persons who she loved to. This spirit conflict made her experienced symptoms of spirit damage such as over anxious and appearing of death instinct. Key words : psychoanalysis, main figure, spirit conflict, anxious, death instinct